Laser therapy, used in a specific dose, modulates pulmonary inflammatory processes in an experimental model of sepsis in rats - Caroline Bublitz; Livia Assis; Ana Cláudia M. Rennó; Vivian Cury; Gabriela Harada; Aya H. Hirai; Liria Yuri Yamauchi (Universidade de São Paulo, 2015)
ABSTRACT This study aimed to determine the effectiveness of LLLT in decreasing the lung inflammatory process in septic rats. A total of 32 male Wistar rats were divided into four groups (n=8): control group (CG), sepsis 24h (S24), sepsis and LLLT with 30 J/cm² (S24L30); sepsis and LLLT with 65 J/cm² (S24L65). The irradiation was performed immediately after surgery in the anterior region of the trachea and ventral regions of the chest, bilaterally, just below the ribs. Histological analysis of lung tissue was performed and the number of inflammatory cells was quantified. The S24 group showed an increase of inflammatory cells compared to the CG (p <0.01); S24L30 increased the number of inflammatory cells, while S24L65 decreased this number compared to S24 (both p<0.05); S24L65 had a lower number of inflammatory cells compared to S24L30 (p<0.01). In conclusion, LLLT at a specific energy dose (30J / cm²) was capable of decreasing the number of inflammatory cells in acute lung tissue inflammation due to sepsis.